Prevention of Noise-Induced Hearing Loss from Recreational Firearms - Meinke, Deanna K.; Finan, Donald S.; Flamme, Gregory A.; Murphy, William J.; Stewart, Michael; Lankford, James E.; Tasko, Stephen (Seminars in Hearing, 2017)
In the United States and other parts of the world, recreational firearm shooting is a popular sport that puts the hearing of the shooter at risk. Peak sound pressure levels (SPLs) from firearms range from ∼140 to 175 dB. The majority of recreational firearms (excluding small-caliber 0.17 and 0.22 rifles and air rifles) generate between 150 and 165 dB peak SPLs. High-intensity impulse sounds will permanently damage delicate cochlear structures, and thus individuals who shoot firearms are at a higher risk of bilateral, high-frequency, noise-induced hearing loss (NIHL) than peer groups who do not shoot. In this article, we describe several factors that influence the risk of NIHL including the use of a muzzle brake, the number of shots fired, the distance between shooters, the shooting environment, the choice of ammunition, the use of a suppressor, and hearing protection fit and use. Prevention strategies that address these factors and recommendations for specialized hearing protectors designed for shooting sports are offered. Partnerships are needed between the hearing health community, shooting sport groups, and wildlife conservation organizations to develop and disseminate accurate information and promote organizational resources that support hearing loss prevention efforts.
Keywords: Impulse noise; firearms; noise-induced hearing loss; hearing loss prevention; hearing conservation; hearing protection